The Influence of Career Development and Work Discipline on Employee Loyalty at Golf Pringgondani Driving Range - Muhammad Rozali; Rezky Oktafiandi; Nicholas; Siti Nabila Putri (SAJMR : Southeast Asian Journal of Management and Research, 2024)
The purpose of this study is to determine the influence of career development and work discipline, both partially and simultaneously, on employee loyalty. This research employs multiple regression. Primary and secondary data collected from field sources and the library are utilized. The research sample consists of 59 employees from the Driving Range Golf Puringondari. The results of this study indicate that Career Development and Work Discipline are important variables influencing Employee Loyalty. The sampling method used is random sampling. This research is quantitative in nature. This method is chosen because the researcher believes it provides equal opportunities for each sampling unit to be selected as a sample, as one of the elements of the population. Primary data is obtained directly through surveys with questionnaires distributed directly to staff at the Driving Range Golf Puringondani. Multiple regression analysis studies what happens to the status (top and bottom) of a dependent variable (criteria) when two or more independent variables are manipulated as predictors (in addition to reducing their values) Used when one wants to make predictions). The results of this study also indicate that the Career Development and Work Discipline variables have a significant influence on Employee Loyalty.